Estimations and asymptotical properties of solutions of weakly nonlinear Volterra intergrodifferential equation of the fourth order with delays. - Iskandarov, S; Temirov, M A (Journal of Mathematics, Mechanics and Computer Science, 2012)
We establish sufficient conditions for estimations, boundedness, a power absolutely integrable on the half-line, tends to zero, including the exponential and power law, all solutions and their first, second, third derivatives of the fourth-order weakly nonlinear Volterra intergo-differential equation.